Boron chemicals in diagnosis and therapeutics. (April 2013) - Das, Bhaskar C; Thapa, Pritam; Karki, Radha; Schinke, Caroline; Das, Sasmita; Kambhampati, Suman; Banerjee, Sushanta K; Van Veldhuizen, Peter; Verma, Amit; Weiss, Louis M; Evans, Todd
Advances in the field of boron chemistry have expanded the application of boron from material use to medicine. Boron-based drugs represent a new class of molecules that possess several biomedical applications including use as imaging agents for both optical and nuclear imaging as well as therapeutic agents with anticancer, antiviral, antibacterial, antifungal and other disease-specific activities. For example, bortezomib (Velcade ® ), the only drug in clinical use with boron as an active element, was approved in 2003 as a proteasome inhibitor for the treatment of multiple myeloma and non-Hodgkin's lymphoma. Several other boron-based compounds are in various phases of clinical trials, which illustrates the promise of this approach for medicinal chemists working in the area of boron chemistry. It is expected that in the near future, several boron-containing drugs should become available in the market with better efficacy and potency than existing drugs. This article discusses the current status of the development of boron-based compounds as diagnostic and therapeutic agents in humans.